Aphrodisiac Activity of Ethanol Extract of Cratoxylum sumatranum (JACK) Blume Stems on Isolated Rat Corpus cavernosum - Sjarif Ismail; Meiliati Aminyoto (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2018)
Cratoxylum sumatranum (Jack) Blume of the Hypericaceae family is known as â€œBentalengâ€ by Dayak Benuaq. In ethnobotany, Cratoxylum sumatranum stems (CSS) is used as energy drink or aphrodisiac, but its effect has not been scientifically proven. Research objective to study the aphrodisiac activity of CSS extract by screening the aphrodisiac activity in vitro. Method: CSS was collected from Kutai Kertanegara Regency, East Kalimantan Province. Extraction was by maceration with ethanol solvent for three days. Re-maceration was done twice. In vitro screening of aphrodisiac activity used isolated rat corpus cavernosum. The organ was placed into a 10 mL chamber containing Krebs-Henselheit solution at pH 7.4, 37Â°C and aerated with carbogen gas. After acclimation, a contraction test was performed with phenylephrine solution and after reaching the peak of contraction at plateau the Control (solvent extract) or CSS ethanol extract was administerd at cumulatively increased concentration. Vasodilation activity was known if the contraction response was decreased after the extractâ€™s administration and expressed in percent contraction with negative value. Results: CSS ethanol extract induce vasodilatory response on rat Corpus cavernosum blood vessels. Vasodilation activity is increasing with increasing concentration of extract given compared to Control. Conclusion the aphrodisiac activity of CSS ethanol extracts is directly through the vasodilation action mechanism on blood vessels in the rat corpus cavernosum.